2023
DOI: 10.7717/peerj.14679
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the breeding phenology of a threatened frog species using eDNA and automatic acoustic monitoring

Abstract: Background Climate change has driven shifts in breeding phenology of many amphibians, causing phenological mismatches (e.g., predator-prey interactions), and potentially population declines. Collecting data with high spatiotemporal sensitivity on hibernation emergence and breeding times can inform conservation best practices. However, monitoring the phenology of amphibians can be challenging because of their cryptic nature over much of their life cycle. Moreover, most salamanders and caecilians do not produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…This important result has at least two explanations. First, DNA can stay up to three weeks in freshwater bodies [56], with variations based on environmental conditions [57]: species seldomly using vernal pools can be detected over a large time window [33]. The second explanation is related to this window of detection, as active search surveys were conducted during the day over short periods, and thus, limiting the chances of detecting species (underlined by the Chao2 index of the traditional methods showing that a higher proportion of species were detected once).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This important result has at least two explanations. First, DNA can stay up to three weeks in freshwater bodies [56], with variations based on environmental conditions [57]: species seldomly using vernal pools can be detected over a large time window [33]. The second explanation is related to this window of detection, as active search surveys were conducted during the day over short periods, and thus, limiting the chances of detecting species (underlined by the Chao2 index of the traditional methods showing that a higher proportion of species were detected once).…”
Section: Discussionmentioning
confidence: 99%
“…Once the eDNA metabarcoding protocol was developed, the laboratory work and data analysis took only days, with a cost per sample of ~CAD$ 33 (for consumables and a Miseq run of 192 samples). Different technologies, such as quantitative or digital PCR, could help in species' specific management plans [33], but metabarcoding can be sufficient on its own or complement the traditional surveys, according to the aims of stakeholders. Regarding the system used here, eDNA could provide the general habitat use data as it reliably detects amphibian species sensitive to habitat modifications and degradations, but difficult to observe with the traditional methods (e.g., N. viridescens, Am.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local factors like rainfall can affect the transport and detection of eDNA in rivers, potentially leading to variations in detection distance and time 15 . Furthermore, climate data, including rainfall, are important in eDNA surveys and data interpretation as rainfall can dilute eDNA concentration and reduce detection probabilities, highlighting the need for repeated sampling and collection of abiotic variables like rainfall 24 . Aucone et al 25 also observed a decrease in eDNA detection in relation to significant heavy rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a behavioural continuum between these two extremes (Wells, 1977;. Several works focused on better describing the breeding acoustic strategies that can be found in anuran species (Chen et al, 2023;Donnelly and Guyer, 1994;Forti et al, 2022;Huang et al, 2001;Prado et al, 2005;Prasad et al, 2022;Bertoluci and Rodrigues, 2002) but there is still missing information mainly for Neotropical anurans. Continuous monitoring of anuran advertisement calls along different spatial-temporal scales, can provide valuable information about the different breeding strategies displayed by each species within an assemblage (Moreira et al, 2007).…”
Section: Introductionmentioning
confidence: 99%